Giovanni Raboni poeta e lettore di poesia (1953-1966) - CHELLA, ANNA (Premio Ricerca «Città di Firenze», 2017)
A poet, critic and translator, Giovanni Raboni is one of the most important figures in the literary panorama of the second half of the 20th Century. This volume sheds light on his twofold journey in the chaotic magma of the 50s and 60s: on the one hand the encounters and discoveries of a passionate and keen critic and reader, on the other the first steps of a young poet in search of his own voice . Young Raboni's path arises from a courageous confrontation with the urgencies of his time, and is nourished by a profound dialogue with "poetry in flesh and blood", "poetry that is made". A path in which the pen of the "poetry reader" often accompanies, with his mild but severe firmness, the poet's free and autonomous hand.